International trade and sustainable development: a circular economy approach - Martínez Prats, Germán (Ingeniería Solidaria, 2025)
Introduction: International trade faces a crucial challenge in achieving sustainable development, which drives the adoption of circular economy strategies. This transition optimizes resource use, minimizes waste, and reduces the environmental impact of global trade.Problem: Despite its benefits, regulatory and technological barriers hinder the implementation of the circular economy in international trade, limiting its contribution to sustainability.Objective: To analyse the relationship between international trade and the circular economy, identifying opportunities and challenges for global sustainability.Methodology: A qualitative approach based on the review of academic literature and case studies was used, allowing for an in-depth exploration of the impact, limitations, and potential of circular economy strategies.Results: The findings indicate that the circular economy reduces the environmental footprint of trade by optimizing resources, reusing materials, and minimizing waste. However, regulatory inconsistencies, technological gaps, and a lack of coordinated policies hinder large-scale adoption.Conclusion: The transition to a circular economy in trade requires multilateral collaboration, robust regulatory frameworks, and public policies that foster sustainable innovation. Without these structural changes, a sustainable and resilient trading system will remain difficult to achieve.Originality: This study explores the intersection between the circular economy and international trade, addressing gaps in policy and implementation research.Limitations: The qualitative approach, while valuable for theoretical and policy analysis, does not include quantitative models of business or environmental impact.